PAJAK DIGITAL DAN PERANG DAGANG ANTARA PERANCIS DENGAN AS - Rizki Hamri Pratama; Yessi Olivia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This study discusses France’s digital tax policy and the trade war between France and the United States (US) that emerged as a result of this policy. The digital tax policy requires digital-based companies with certain incomes operating in France to pay taxes to the French government. The US considered this policy as a discrimination towards US based digital companies and threatened to impose 100% import duties on French products. France’s position to continue implementing its digital tax policy even though the US has threatened to increase tariffs on French products is the focus of this researchThis research is an explanatory qualitative research that emphasizes on the depth of the data obtained by the researcher. The theory used to analyze the thesis case study is economic nationalism. The assumption of this theory is that the economy cannot be separated from politics.  Mercantalism assumes that the state is the main actor who continues to strive to achieve the interests of the country by all means including economic means. Therefore, each country has a role to protect the interests of each country.This study shows the reason why France continues to enforce its digital tax policy is because France wanted to increase the country’s revenue from the digital economy activities. The support coming from other European Union countries has strenghtened France’s position to carry out the digital tax policy..Keyword: digital tax policy, economic nationalism, trade war, digital economy